2019
DOI: 10.1038/s41598-019-47238-w
|View full text |Cite
|
Sign up to set email alerts
|

Healthy ageing trajectories and lifestyle behaviour: the Mexican Health and Aging Study

Abstract: Projections show that the number of people above 60 years old will triple by 2050 in Mexico. Nevertheless, ageing is characterised by great variability in the health status. In this study, we aimed to identify trajectories of health and their associations with lifestyle factors in a national representative cohort study of older Mexicans. We used secondary data of 14,143 adults from the Mexican Health and Aging Study (MHAS). A metric of health, based on the conceptual framework of functional ability, was mapped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 45 publications
6
52
2
1
Order By: Relevance
“…Whilst most of the population exhibited a stable trajectory at a high level of health, we found two subgroups with alternative trajectories: one with a stable lower level of health; and a third subgroup starting at a similar point as the majority of the population but whose health severely deteriorated over time. These results were similar to those reported in previous studies in terms of the number and shape of the different trajectories [9,29,30], although in some of these studies the declining trajectories comprised a higher percentage of the population. Our findings were replicated in the sensitivity analyses, supporting the existence of heterogeneity in ageing trajectories and the importance of accounting for this heterogeneity when studying healthy ageing [3,4].…”
Section: Interpretation Of Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…Whilst most of the population exhibited a stable trajectory at a high level of health, we found two subgroups with alternative trajectories: one with a stable lower level of health; and a third subgroup starting at a similar point as the majority of the population but whose health severely deteriorated over time. These results were similar to those reported in previous studies in terms of the number and shape of the different trajectories [9,29,30], although in some of these studies the declining trajectories comprised a higher percentage of the population. Our findings were replicated in the sensitivity analyses, supporting the existence of heterogeneity in ageing trajectories and the importance of accounting for this heterogeneity when studying healthy ageing [3,4].…”
Section: Interpretation Of Findingssupporting
confidence: 92%
“…fast decline) was relatively low, which led to wider confidence intervals. Finally, although recent research on low-and middle-income countries has found results that are consistent with the evidence presented in our study [9,24], it is important to note that most of the countries included in this study were high-income countries. As a result of these limitations, extra caution is needed when generalising these findings.…”
Section: Strengths and Limitationssupporting
confidence: 92%
See 1 more Smart Citation
“…Healthy lifestyles, including during midlife, have been proven to be associated with good overall health during aging.However, we could not determinethe associations between remaining sociodemographic and behaviour variables and SA in the present study. This is inconsistent with previous studies [26][27].A possible explanation for the discrepancy is that the majority of our respondents were female and it is not the norm for Malaysian women to smoke or drink alcohol due to socio-cultural environmentalinfluence [28].…”
Section: Resultscontrasting
confidence: 98%
“…Ageing is not a problem confined to the most economically developed countries. Malaysia will become a country of people who are predominantly elderly by 2035; In Mexico, the elderly population will have a higher percentage of growth than other Latin American countries by 2050 [5,6]. Tunisia is experiencing an increase in the elderly population and a decrease in overall population growth [7].…”
Section: Introductionmentioning
confidence: 99%